The patient journey project in Italian mental health services: results from a co-designed survey on clinical interventions and current barriers to improve the care of people living with schizophrenia - Vita, Antonio; Barlati, Stefano; Porcellana, Matteo; Sala, Elisa; Lisoni, Jacopo; Brogonzoli, Luisa; Percudani, Mauro Emilio; Iardino, Rosaria (Frontiers in Psychiatry, 2024)
We thank the Reviewer 1 for this suggestion. As previously reported, we moved this sentence in the section 2.2. Statistical analyses.8. Discussion, page 19, lines 6-9, the sentence "Studies like this are important…." underly the importance to investigate differences among regions. However, in this paper no data are described on the differences among regions. Therefore, the sentence should be modified accordingly. The same applies on page 22, lines 16-19, where heterogeneous implementation levels in clinical practice are cited.We thank the Reviewer 1 for this suggestion. We have modified these pieces accordingly, as follows:"Studies like this are important to provide an overview, at a national level, on the care of PLWS as the national MHS situation may indirectly reflect what happens at a regional level, where the organization of local MHS could substantially differ due to inter-regional difference in resources allocation (especially for what concerns the access and intensity of psychosocial care).""However, this is only a suggestion as this study did not systematically investigate inter-regional differences between local MHS. Moreover, no other studies are available to compare our results, except for our previous survey that examined the Lombardy MHDAS [35]."